2010
DOI: 10.1159/000279307
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Sildenafil Treatment Corrects Endothelial Dysfunction and Improves Hypertension

Abstract: Background: Nitric oxide (NO) availability plays a critical role in the regulation of blood pressure, endothelial function and arterial structure. Many of the biological actions of NO are mediated by 3′5′-guanosine monophosphate (cGMP), which is rapidly degraded by cGMP phosphodiesterase (PDE). Short-term cardiovascular effects of PDE inhibitors have been studied but the changes resulting from their chronic administration in hypertension have not been evaluated. We investigated if retarding the degradation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 65 publications
2
13
0
2
Order By: Relevance
“…NO exerts many of the biological actions via cGMP, which is rapidly degraded by cGMP PDE. Thus, PDEi has the potential to improve the endothelial function, which has been shown in animal and clinical studies [710]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NO exerts many of the biological actions via cGMP, which is rapidly degraded by cGMP PDE. Thus, PDEi has the potential to improve the endothelial function, which has been shown in animal and clinical studies [710]. …”
Section: Discussionmentioning
confidence: 99%
“…However, there are plenty of studies reporting the safe use of PDE-5 inhibitors in humans, including those evaluating the effect of PDE-5 inhibitors on the coronary arteries in humans[1012]. There exist at least 11 isoforms of PDE, and the differential distribution of PDE isoforms in various tissues is the basis for the potential tissue-specific effect of a PDE inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As determined by tail-cuff plethysmography as well as by direct intra-arterial determinations (fig. 1a, b), sildenafil treatment ameliorated hypertension, an effect that is observed in rats treated chronically with this drug [7,24] but not regularly in short-term studies [25,26,27]. To determine whether reduction of the blood pressure would by itself play a role in the beneficial effects of sildenafil, we studied the rats of the TRX group that despite normalization of blood pressure had no improvement in the remnant kidney glomerular hemodynamics or histological damage.…”
Section: Discussionmentioning
confidence: 99%
“…Because there are only single-dose studies to evaluate, it is unclear as to whether the observed BP lowering with this combination reflects a physiological rather than a pharmacological effect on the NO-cGMP pathway or whether it is a byproduct of rectifying the endothelial dysfunction common in difficult-to-treat hypertension. 8,9 Moreover, this combination would be of the greatest use in patients having failed other more traditional therapies for the resistant hypertensive, such as spironolactone. These 2 drugs given together are not necessarily a benign combination, and there will be a subset of excessive responders raising for consideration whether the first time the combination is given that it is under supervised conditions.…”
mentioning
confidence: 99%